Zonisamide effects on sleep problems and depressive symptoms in Parkinson's disease. Issue 3 (5th January 2021) - Suzuki, Keisuke; Fujita, Hiroaki; Matsubara, Takeo; Haruyama, Yasuo; Kadowaki, Taro; Funakoshi, Kei; Watanabe, Yuji; Hirata, Koichi
Abstract: Background: We aimed to evaluate the effect of zonisamide (ZNS) on motor symptoms and nonmotor symptoms such as depressive symptoms and sleep problems in Parkinson's disease (PD) patients with or without tremor. Methods: We conducted a 3‐month, open‐label study to assess the effects of ZNS on motor symptoms, depressive symptoms and sleep problems. Twenty levodopa‐treated PD patients with motor fluctuation completed the study. Patients received 25–50 mg/day of ZNS and were assessed for the Japanese version of the Movement Disorder Society Revision of the Unified PD Rating Scale (MDS‐UPDRS) parts I, III, and IV, PD Sleep Scale (PDSS)‐2, Beck depression inventory‐2 (BDI‐II), and PD Questionnaire (PDQ‐8) at baseline and after 1, 2 and 3 months of treatment. Patients were categorized into the tremor group and nontremor group to assess changes in clinical parameters. Results: At 3 months, the scores on the MDS‐UPDRS parts I, III and IV significantly improved and off‐time reduced compared to baseline. Additionally, the PDSS‐2 total score significantly decreased at 3 months. Although there were no significant differences in changes in UPDRS part I, III, or IV between the groups after ZNS treatment, the tremor group had significant improvements in PDSS‐2 at 3 months and BDI‐II at 1, 2 and 3 months compared with the nontremor group. Conclusion: We showed the beneficial effects of ZNS on motor symptoms and sleep problems in levodopa‐treated PD patients with motor fluctuation. ZNS may be more effective for several nonmotor symptoms in PD patients with tremor compared with those without tremor. Abstract : In this 3‐month open‐label study, we showed the beneficial effects of zonisamide (ZNS) on motor symptoms and sleep problems in levodopa‐treated PD patients with motor fluctuation. ZNS was more effective for sleep disturbances and depressive symptoms in PD patients with tremor compared with those without tremor.